Worship Music & Culture : The Case of the Songhai of Niger - DeValve, John R. (Book collections on Project MUSE., 2020)
"Music is an exciting aspect of African cultures south of the Sahara, abounding in creativity and full of life and movement. Christian worship music was added to the music mix by missionaries from Europe and North America in the nineteenth and twentieth centuries, and it has retained much of its Western flavor. This book is a case study of the African Christian community among the Songhai and its worship music. Drawing on extensive research conducted over a six-year period, the author explains the relationships between music, culture, and worship using the Songhai church as a case study. In the process, he builds a model for further research and experimentation in the worship of other Christian communities. Included in the discussion are insights from the disciplines of ethno- musicology, worship study, anthropology, theology, missiology, and history."--Publisher